(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article describes the dialogue between Latin American (post)vanguard narrative and the figure of the accident during the twentieth century. We propose a model of analysis that examines the assimilation of this socio-cultural phenomenon in terms of literary structure, reception and content. We propose a reading model based on the insightful contributions of Macedonio Fernandez’s Museo de la Novela de la Eterna, and analyze the political-aesthetical figuration of the accident in a corpus of exemplary texts.